Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1955
DOI: 10.1119/1.1934006
|View full text |Cite
|
Sign up to set email alerts
|

The Néel Theory of Ferrimagnetism

Abstract: The Néel theory of ferrimagnetism is a molecular-field theory of magnetic ordering in systems which contain nonequivalent substructures of magnetic ions. The two principal results of the theory are (a) the curve of reciprocal susceptibility vs temperature above the Curie temperature is an hyperbola, and (b) the curve of spontaneous magnetization vs temperature below the Curie temperature may have any one of a number of unusual forms. The exact form depends on the distribution of magnetic ions between the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1
2

Year Published

1970
1970
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(60 citation statements)
references
References 0 publications
7
48
1
2
Order By: Relevance
“…As to saturation magnetization, it increases with ZrO 2 addition increasing and reaches the maximum of 1936 × 10 −4 T at x = 0.3, which is followed by a decrease when x is 0.4. Based on Neel's theory of ferrimagnetism in ferrites [25], the substitution of a non-magnetic ion like Zr 4+ in [a] site can lead to the rise of total saturation magnetization. However, the observed decline in saturation magnetization for the sample with x = 0.4 may be attributed to the formation of a special d site when the addition of Zr 4+ surpasses a critical limit (x = 0.3), in which all the magnetic positive ions will lose the object of superexchange interaction because of the position occupied by Zr 4+ .…”
Section: Phase Analysis and Sintering Charactermentioning
confidence: 99%
“…As to saturation magnetization, it increases with ZrO 2 addition increasing and reaches the maximum of 1936 × 10 −4 T at x = 0.3, which is followed by a decrease when x is 0.4. Based on Neel's theory of ferrimagnetism in ferrites [25], the substitution of a non-magnetic ion like Zr 4+ in [a] site can lead to the rise of total saturation magnetization. However, the observed decline in saturation magnetization for the sample with x = 0.4 may be attributed to the formation of a special d site when the addition of Zr 4+ surpasses a critical limit (x = 0.3), in which all the magnetic positive ions will lose the object of superexchange interaction because of the position occupied by Zr 4+ .…”
Section: Phase Analysis and Sintering Charactermentioning
confidence: 99%
“…16 A detailed study of the Néel theory of ferrimagnetism was first given in 1955 by Smart. 32 A possible explanation for the P-type ferrimagnetism of Mn 3 Ge is the different behavior of the two magnetic Mn species on the 2b and 4d sites. Assuming that the magnetic moment on the 4d site is less sensitive to thermal activation than that of Mn on the 2b site, a resulting increase in the total moment would result, which is the characteristic of P-type ferrimagnetism.…”
mentioning
confidence: 99%
“…It is observed that, the magnetic properties such as saturation magnetisation (Ms), remnant magnetisation (Mr) and coercivity (Hc) values are gradually decreasing with the increase of bismuth ion concentration and the values are listed in [28]. This is due to the cation distribution in between A and B sub lattices which were proposed by Neel's two sub lattice model [29] [30]. According to this, in any ferrite the magnetic order of tetrahedral clusters (A-site) and octahedral clusters (B-site) was found to be anti parallel to each other.…”
Section: Xrd Analysismentioning
confidence: 87%